A case of mixed gonadal dysgensis: A diagnostic challenge - Uma Kaimal Saikia; Dipti Sarma; Darvin Vamadevan Das; J K Goswami; Kaushik; Chandan Saikia; Abilash Nair (Wolters Kluwer Medknow Publications, 2019)
A 2-year-old child reared as a girl child was brought by parents with ambiguous genitalia noticed since birth. There was no history of failure to thrive or salt-losing crisis. On examination, the child had normal height and weight with normal blood pressure and no dysmorphism or Turners stigmata with external genitalia Prader Score 2. Ultrasound of the pelvis revealed hypoplastic uterus with no gonads visualized. There was no evidence of hypocortisolemia (8 am cortisol 14.08 mcg/dl) or elevated level of 17-OH-progesterone (1.1 ng/mL). Pooled follicle-stimulating hormone and luteinizing hormone levels were 2.66 mIU/ml and 0.1 mIU/ml, respectively, thyroid-stimulating hormone: 2.36 mIU/L, T4: 134.5 nmol/L, total testosterone: 2.5 ng/dl. Posthuman chorionic gonadotropin stimulation showed total testosterone levels 267 ng/dL, dihydrotestosterone: 155 pg/mL, androstenedione: 0.3 ng/mL indicating functioning testicular tissue without any evidence of 17-beta hydroxylase or 5-alpha reductase deficiency. Karyotyping revealed 45, XO genotype on two separate occasions. In view of the discrepancy between karyotype finding and ultrasound reports with the clinical and hormonal picture, fluorescence in situ hybridization cytogenetic study was carried out and showed MONOSOMY X (90% cells)/SEX ANEUPLOIDY XYY (10% cells). Laparoscopic examination showed gonad in the right ovarian fossa and left streak gonad with bilateral fallopian tubes and hypoplastic uterus. Genitoscopy showed normal vagina and cervix. Cystoscopy showed normal urethra and urinary bladder. Biopsy was taken from both gonads. A thorough histopathological examination of this specimen showed the structure of seminiferous tubules with Leydig cells in the right gonad with streak ovary on the left side. The child underwent bilateral gonadectomy and rehabilitated her to lead a life as a girl.